Association between cumulative biological risk and hypertension in older adults in Korea: a population-based cross-sectional study - Hyemin Hwang; Kyeongmin Jang (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study examined the association between cumulative biological risk and hypertension among older adults in Korea using nationally representative data. Methods: Data were obtained from the 2024 Korea National Health and Nutrition Examination Survey, the most recent dataset released in December 2025. The main analytic sample included 1,551 adults aged 65 years or older. The cumulative biological risk score (CBRS) was calculated using five indicators: anemia, elevated glycated hemoglobin, obesity defined as body mass index ≥ 25 kg/m², elevated high-sensitivity C-reactive protein, and vitamin D deficiency. Hypertension was defined as self-reported physician-diagnosed hypertension. Complex sample analyses incorporated sampling weights, stratification variables, and cluster variables. Complex sample logistic regression was performed using IBM SPSS Statistics version 30.0.Results: CBRS showed a graded association with hypertension across risk categories. Compared with the low-risk group, the moderate-risk group had higher odds of hypertension (odds ratio [OR] = 1.67, 95% confidence interval [CI]: 1.16–2.40), and the high-risk group had still higher odds (OR = 2.92, 95% CI: 1.87–4.54). Age, monthly alcohol use, and absence of aerobic physical activity were also associated with higher odds of hypertension. Conclusion: Cumulative biological risk was significantly associated with hypertension among older adults in Korea, suggesting that hypertension in later life may be related to accumulated biological dysregulation. An integrated assessment of multiple biological and metabolic abnormalities may help characterize clustered biological vulnerability and support comprehensive preventive nursing care.